PENINGKATAN KINERJA GURU MADRASAH MELALUI PENERAPAN STRATEGI PEMBELAJARAN BERVARIASI - Nurmala, Ela (Perkumpulan Sarjana Manajemen Pendidikan Islam Indonesia, 2019)
Based on the results of the Competency Knowledge Test (UPK) specifically regarding writing skills in class XI religious (IIK)-1 state madrasa aliyah (MAN) 2 Sumedang, it turns out that from the total of 34 students only 15 people or 42.86% whose value exceeds the specified Minimum Completion Criteria (KKM) value limit that is 78. This shows that learning achievement in English, especially writing skills in class IIK-1 is still low. The facts above show that students' learning achievement in English subjects is still low. One way out is to change the learning model by applying the Picture Word Inductive Model Strategy learning model to English subjects. This study aims to describe the application of the Picture Word Inductive Model Strategy in improving learning activities and Educator Performance and learning outcomes of English Class XI Religious (IIK) -1 MAN 2 Sumedang Students Even Semester Academic Year 2016/2017. From the results of the research conducted in March, May 2017 with 2 cycles there are the following findings: The increase in the performance value of educators from cycle 1 to cycle 2 increased by 10 points while from cycle 2 to cycle 3 increased by 8 points. Furthermore, in terms of categories also increased from C in cycle 1, B to cycle 2 and A in cycle 3. The increase in this activity value from cycle 1 to cycle 2 increased by 9.99 points while from cycle 2 to cycle 3 increased by 7.53 points . Furthermore, in terms of categories also increased from C in cycle 1, B in cycles 2 and A in cycle 384 to 82.54 on average cycle 2 learning achievement. An increase in learning achievement from cycle 1 to cycle 2 increased by 9.99 points while from cycle 2 to cycle 3 increased by 7.53 points. Furthermore, in terms of categories also increased from C in cycle 1, B in cycles 2 and A to cycle 3. Based on the findings in the research above, it can be concluded that: the increase in learning achievement from cycle 1 to cycle 2 increased by 9.99 point while from cycle 2 to cycle 3 increased by 7.53 points. Furthermore, in terms of categories also increased from C in cycle 1, B in cycles 2 and A in cycle 317